Assembly and structure of the SSU processome — a nucleolar precursor of the small ribosomal subunit. (April 2018) - Barandun, Jonas; Hunziker, Mirjam; Klinge, Sebastian
Graphical abstract: Highlights: A decade after its discovery, the structure of the small subunit processome emerges. More than 50 proteins and a snoRNA remodel pre-ribosomal RNA in the SSU processome. Initially, flexible assembly factors guide the formation of a rigid scaffold. rRNA domains are kept separate to facilitate their modification and processing. Rearrangements and compaction of rRNA domains are required to form the mature SSU. Abstract : The small subunit processome is the first precursor of the small eukaryotic ribosomal subunit. During its assembly in the nucleolus, many ribosome biogenesis factors, an RNA chaperone, and ribosomal proteins associate with the nascent pre-rRNA. Biochemical studies have elucidated the rRNA-subdomain dependent recruitment of these factors during SSU processome assembly and have been complemented by structural studies of the assembled particle. Ribosome biogenesis factors encapsulate and guide subdomains of pre-ribosomal RNA in distinct compartments. This prevents uncoordinated maturation and enables processing of regions not accessible in the mature subunit. By sequentially reducing conformational freedom, flexible proteins facilitate the incorporation of dynamic subcomplexes into a globular particle. Large rearrangements within the SSU processome are required for compaction into the mature small ribosomal subunit.